(3QSGdI aj MOhK GdCLSGes
(3ChdgG (B:s
(3GNJda Cgd GdYde ai MOhK GdGLSGe hGdhLhg GdeMJedI CeG GdChd abO bGd GdeSdehf hGdfUGQi hGdjghO hGdeLhS aCfge bGdhG GdGLSGe eMOKI HPhGJgG s
(3BNQgG (B:s
(3aMOK GdSehGJ hGdYfGS Ke MOK ai GdMQcGJ GdSeGhjI GeJRGLGJ gPg GdYfGS hefgG gPg GdeQcHGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3GfXQg eY GdeNWhW Qbe (B292s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs